Anabolic steroids and pre-adolescent athletes: prevalence, knowledge, and attitudes - Wroble, R. R.; Gray, M.; Rodrigo, J. A. (The Sport Journal, 2002)
Objective. To determine the prevalence, knowledge, and attitudes regarding anabolic steroids among pre-adolescent athletes and to compare our findings with a similar survey done in 1989. Design. A survey of 1,553 pre-adolescent (10 to 14 year-old) athletes from 34 states. Results. Less than one percent (0.7%) of the study group reported current or previous anabolic steroid usage. Eighty-eight percent had heard of anabolic steroids, but only 64% had had their side effects explained to them. Only 47% stated that a parent, coach, teacher, or athletic trainer was their primary source of information. Results were compared to a 1989 baseline study completed before legislation lead to the scheduling of anabolic steroids. In 1989, 78% had heard of anabolic steroids, 50% had had the side effects explained to them, and 2% admitted to using steroids. Conclusions. These results suggest that anabolic steroids remain a problem among pre-adolescents. Educational programs should be instituted during junior high school to increase the knowledge of anabolic steroids in this group. Information should come from qualified individuals including coaches, teachers, trainers, and especially parents.